The Use Of Whatsapp Messaging As One Of Mobile Learning On Students’ Writing Skill Error - Alfitriani Siregar; Miss Rohani Pooteh; Idris Eal Al Amini; Putri Isnin Suryaningsih Hia (Yayasan Literasi Sains Indonesia, 2022)
The purpose of the study was to analyze the use of WhatsApp messaging as one of mobile learning on students' errors in writing recount texts with the theme